The establishment and functioning of the PRIMORE (European PRImary care MultiprOfessional REsearcher network) Project - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2019)
There is a need for multiprofessional comprehensive studies to better understand the relationship between design and provision of primary care and long-term care and health outcomes. The PRIMORE (PRImary care MultiprOfessional REsearcher network) project aims at bringing together researchers with different backgrounds and from a wide range of professional groups within the fields of primary care research and long-term care research to develop and share knowledge for the benefit of research on municipal health and care services, and eventually, the quality of municipal health and care in Europe. Main activities of the project will be network development, capacity building, providing a platform where multiprofessional primary care research activities can take place and publishing position papers.
Keywords: primary health care; research; policy; HEALTH